Don't repeat mistakes of past year - Abd Razak, Dzulkifli (2008)
THIS column enters its 13th year this week. Many opinions have been expressed during these years, so too during the exchanges and engagements with fellow readers. Many are very memorable, some are indeed most inspiring. This time is no different. Some of the memories experienced last year are difficult to let go. They have created such a keen impact. Fifty years of nationhood is one such instance. The other is, of course, the launching of the first Malaysian angkasawan. Both gave us a sense of pride, strength and inspiration.